Community Structure of Phyllosphere Bacteria in Different Cultivars of Fingered Citron (Citrus medica ‘Fingered’) and Their Correlations With Fragrance - Wang, Yi; Wu, Jiaqi; Sun, Ping; Chen, Chenfei; Shen, Jiansheng (Frontiers in Plant Science, 2022)
In recent years, plant metabolomics and microbiome studies have suggested that the synthesis and secretion of plant secondary metabolites are affected by microbial-host symbiotic interactions. In this study, six varieties of fingered citron (Citrus medica 'Fingered') are sampled to study their phyllosphere bacterial communities and volatile organic compounds (VOCs). High-throughput sequencing is used to sequence the V5–V7 region of the 16S rRNA of the fingered citron phyllosphere bacteria, and the results showed that Proteobacteria, Actinobacteria, Firmicutes, and Bacteroidetes were the dominant bacterial phylum in the phyllosphere of fingered citron. There were significant differences in the phyllosphere bacteria community between XiuZhen and the remaining five varieties. The relative abundance of Actinomycetospora was highest in XiuZhen, and Halomonas, Methylobacterium, Nocardioides, and Pseudokineococcus were also dominant. Among the remaining varieties, Halomonas was the genus with the highest relative abundance, while the relative abundances of all the other genera were low. Headspace solid-phase microextraction (HS-SPME) and gas chromatography-mass spectrometry (GC-MS) were used to analyze and identify the aroma compounds of six different fingered citron, and a total of 76 aroma compounds were detected in six varieties. Pinene, geraniol, and linalool were found to be the primary VOCs that affect the aroma of fingered citron based on relative odor activity value. The correlation analysis showed 55 positive and 60 negative correlations between the phyllosphere bacterial flora and aroma compounds of fingered citron. The top 10 genera in the relative abundance were all significantly associated with aroma compounds. This study provides deep insight into the relation between bacteria and VOCs of fingered citron, and this may better explain the complexity of the analysis of bacterial and metabolic interactions.